A triple whammy: how urban heat, housing unaffordability and disadvantage affect urban spatial resilience - Herath, Shanaka; Cilliers, Elizelle Juanee; Mussi, Eveline (Frontiers in Sustainable Cities, 2024)
Climate change generates multiple negative impacts for cities, such as the urban heat island effect. Social stresses, including social disadvantage and housing unaffordability, compound the poor living conditions of urban residents and make our cities less resilient. This paper considers a climate event (urban heat) and social stresses (housing affordability and urban disadvantage) to explore urban resilience in Sydney. We draw on a framework for building urban climate resilience, incorporating facets of urban resilience, social stresses that amplify crises, and solutions that strengthen individuals and communities with coping abilities to withstand climate events. The study diverges from aggregate city-level analyses that hide small-area differences of in climate impacts and vulnerability. The findings reveal the spatiality of these natural and social impacts, identifying 11 critical areas in Sydney impacted by the highest levels of urban heat and urban disadvantage, and two critical areas impacted by the highest levels of urban heat and housing unaffordability. We highlight the importance of context-based approaches and place-based policies to address climate risks and social vulnerabilities on the path towards creating more resilient cities.